The Role of Time in the Theory of Narrative Identity in the Philosophy of Paul Ricoeur - Michał Kumorek (RUDN Journal of Philosophy, 2021)
Time has a very important function in considering the identity of a person. It is the factor that brings identity into question. The core of the problem is the question of whether the person is the same as he or she was at another time. The problem of personal identity was one of the most important issues in Paul Ricoeurs philosophy. He considers this problem in the context of time and notes that traditional models of identity as sameness and as selfhood have been entangled in various aporias. He, therefore, proposes two new models of identity that are related in different ways to temporality: character and promise. Character is a model that changes over time through the acquisition or loss of various traits. The promise, on the other hand, is a model that resists the pressure of time attempts to keep a given word. In this way, these two different models create the framework for Ricoeur's concept of narrative identity. In this concept, time enables the development of action in a story. It allows the action to turn around, but it also allows the human being to look at the story of his or her life. Character and promise are models that allow the human being to look at his or her life as a certain temporal entity that is constantly threatened by unforeseen accidents and events but also constantly absorbs them and, through to time, gives the possibility of retrospection leading to synthesis. This synthesis allows us to look at a single life as a whole, belonging to the same person endowed with the character and challenge of keeping a promise.